Battery and manufacturing method thereof

The battery design with a Li-Mg and Li-In alloy phase metal layer in the anode reaction enhances discharge capacity by maintaining ion conductivity, addressing the discharge capacity limitations in existing lithium deposition-dissolution batteries.

JP2025044755AActive Publication Date: 2025-04-02TOYOTA JIDOSHA KK
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
JP2023152509
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Filing Date
2023-09-20
Publication Date
2025-04-02
Estimated Expiration
2043-09-20

AI Technical Summary

Technical Problem

Batteries utilizing a deposition-dissolution reaction of metallic lithium as the anode reaction lack sufficient discharge capacity characteristics.

Method used

A battery design with a metal layer containing a Li-Mg alloy phase and a Li-In alloy phase, arranged in a specific order with a solid electrolyte layer, where the Li-In alloy phase is dispersed in the Li-Mg alloy phase, enhancing ion conductivity and suppressing resistance.

Benefits of technology

The battery achieves improved discharge capacity characteristics by maintaining a high ion conduction path through the Li-In alloy phase, ensuring good discharge capacity and retention.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025044755000001_ABST
    Figure 2025044755000001_ABST
Patent Text Reader

Abstract

To provide a battery having good discharge capacity characteristics.SOLUTION: A battery that utilizes a deposition and dissolution reaction of metallic lithium as an anode reaction includes an anode current collector, a metal layer, an electrolyte layer, and a cathode active material layer in this order in the thickness direction, the metal layer contains a Li-Mg alloy phase and a Li-In alloy phase.SELECTED DRAWING: Figure 1
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present disclosure relates to batteries and methods for making the same. [Background technology]

[0002] A battery usually has an electrolyte layer between a positive electrode active material layer and a negative electrode active material layer. In the field of batteries, batteries that utilize a deposition-dissolution reaction of metallic lithium as a negative electrode reaction are known. For example, Patent Document 1 discloses an all-solid-state battery that utilizes a deposition-dissolution reaction of metallic lithium as a negative electrode reaction. [Prior art documents] [Patent documents]

[0003] [Patent Document 1] JP 2020-184513 A Summary of the Invention [Problem to be solved by the invention]

[0004] In a battery that uses a precipitation / dissolution reaction of metallic lithium as the anode reaction, a typical anode active material layer (a layer containing anode active material particles that absorb and release Li) is not usually provided during battery production, and anode active material layer (Li-containing layer) is formed by initial charging, which has the advantage of making it easier to improve energy density. On the other hand, there is room for further improvement in the discharge capacity characteristics of batteries that use a precipitation / dissolution reaction of metallic lithium as the anode reaction.

[0005] The present disclosure has been made in view of the above-mentioned circumstances, and has as its main object to provide a battery having good discharge capacity characteristics. [Means for solving the problem]

[0006] [1] A battery that utilizes a deposition and dissolution reaction of metallic lithium as a negative electrode reaction, The negative electrode current collector, the metal layer, the electrolyte layer, and the positive electrode active material layer are arranged in this order in the thickness direction, The battery, wherein the metal layer contains a Li-Mg alloy phase and a Li-In alloy phase.

[0007] [2] The battery according to [1], wherein in the metal layer, the Li—In alloy phase is dispersed in the Li—Mg alloy phase.

[0008] [3] The battery according to [1] or [2], wherein in the metal layer, a ratio of In to a total of In and Mg is 5 at % or more and 60 at % or less.

[0009] [4] The battery according to any one of [1] to [3], wherein in the metal layer, a ratio of In to a total of In and Mg is 25 at % or more and 60 at % or less.

[0010] [5] The battery according to any one of [1] to [4], wherein the size of the Li-Mg alloy phase is 0.1 μm or more and 5 μm or less.

[0011] [6] The battery according to any one of [1] to [5], wherein the metal layer does not contain a binder.

[0012] [7] The battery according to any one of [1] to [6], wherein the electrolyte layer is a solid electrolyte layer containing a solid electrolyte.

[0013] [8] The battery according to any one of [1] to [7], wherein the solid electrolyte is a sulfide solid electrolyte.

[0014] [9] A battery that utilizes a deposition and dissolution reaction of metallic lithium as a negative electrode reaction, The negative electrode current collector, the metal layer, the electrolyte layer, and the positive electrode active material layer are arranged in this order in the thickness direction, The battery, wherein the metal layer comprises a Mg-In alloy.

[0015]

[10] The battery according to [9], wherein the metal layer has a metal phase of the Mg—In alloy (Mg—In alloy phase).

[0016]

[11] The battery according to [9] or

[10] , wherein the metal layer is a vapor deposition layer.

[0017]

[12] The battery according to [9], wherein the metal layer contains particles of the Mg—In alloy.

[0018]

[13] A method for manufacturing a battery using a deposition / dissolution reaction of metallic lithium as a negative electrode reaction, a metal layer forming step of forming a metal layer including an Mg-In alloy phase by a deposition method; an assembling step of assembling the battery having a negative electrode current collector, the metal layer, an electrolyte layer, and a positive electrode active material layer in this order in a thickness direction; A method for manufacturing a battery comprising the steps of:

[0019]

[14] The method for producing a battery according to

[13] , further comprising a charging step of charging the battery after the assembling step, to form a Li-Mg alloy phase and a Li-In alloy phase from the Mg-In alloy phase contained in the metal layer. Effect of the Invention

[0020] The battery according to the present disclosure has an advantage of having good discharge capacity characteristics. [Brief description of the drawings]

[0021] [Figure 1] FIG. 1 is a schematic cross-sectional view illustrating a battery according to the present disclosure. [Diagram 2] FIG. 2 is an explanatory diagram illustrating a state during charging of a battery according to the present disclosure. [Diagram 3]FIG. 2 is an explanatory diagram illustrating a state of a battery during discharging according to the present disclosure. [Figure 4] FIG. 1 is a flow diagram illustrating a method for manufacturing a battery in the present disclosure. [Diagram 5] 1 shows the results of charge / discharge tests on the evaluation cells produced in Examples 1 to 5 and Comparative Examples 1 and 2. [Figure 6] 1 shows the results of charge / discharge tests on the evaluation cells produced in Examples 1 to 5 and Comparative Examples 1 and 2. [Figure 7] 1 is a cross-sectional SEM image of the evaluation cell produced in Example 3. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0022] Hereinafter, the battery and the manufacturing method thereof according to the present disclosure will be described in detail with reference to the drawings. Each of the drawings shown below is a schematic illustration, and the size and shape of each part are appropriately exaggerated for ease of understanding.

[0023] A.Battery Fig. 1 is a schematic cross-sectional view illustrating a battery according to the present disclosure. Specifically, Fig. 1(a) is a schematic cross-sectional view illustrating a battery before the first charge, and Fig. 1(b) is a schematic cross-sectional view illustrating a battery after the first charge.

[0024] As shown in FIGS. 1(a) and 1(b), the battery 10 includes a negative electrode current collector 1, a metal layer 2, an electrolyte layer 3, and a positive electrode active material layer 4 arranged in a thickness direction D T In the above, the positive electrode current collector 5 is disposed on the opposite side of the electrolyte layer 3 with respect to the positive electrode active material layer 4. As shown in FIG. 1(a), the metal layer 2 in the battery 10 before the first charge contains an Mg-In alloy. The metal layer 2 is typically a deposition layer having an Mg-In alloy phase. On the other hand, when the battery 10 shown in FIG. 1(a) is charged, the Mg-In alloy phase reacts with Li, and the Mg-In alloy phase is converted into a Li-Mg alloy phase and a Li-In alloy phase. As shown in FIG. 1(b), the metal layer 2 in the battery 10 after the first charge contains a Li-Mg alloy phase and a Li-In alloy phase.

[0025] According to the present disclosure, since the metal layer contains Mg and In, the battery has good discharge capacity characteristics. As described above, in a battery using the deposition and dissolution reaction of metallic lithium as the negative electrode reaction, a general negative electrode active material layer (for example, a layer containing negative electrode active material particles that absorb and release Li) is not usually provided during the preparation of the battery, and the negative electrode active material layer (Li-containing layer) is formed by the initial charge, which has the advantage that the energy density can be easily improved. On the other hand, there is room for further improvement in the discharge capacity characteristics of a battery using the deposition and dissolution reaction of metallic lithium as the negative electrode reaction.

[0026] In contrast, in the present disclosure, a metal layer containing Mg and In is used. By using such a metal layer, good discharge capacity characteristics can be obtained. It is presumed that the reason why good discharge capacity characteristics can be obtained is that the use of a metal layer containing Mg and In can suppress the increase in resistance in the negative electrode at the end of discharge. Hereinafter, the effects obtained in the present disclosure will be described in detail with reference to FIG. 2 and FIG. 3.

[0027] As shown in FIG. 2(a), the battery 10 has a negative electrode current collector 1, a metal layer 2, an electrolyte layer 3, a positive electrode active material layer 4, and a positive electrode current collector 5 in this order in the thickness direction. The metal layer 2 has an Mg-In alloy phase. Next, as shown in FIG. 2(b), when charging of the battery 10 is started, a Li-In alloy phase is first formed from a part of the Mg-In alloy phase. Since In has a higher reaction potential for Li insertion / extraction than Mg, In reacts with Li before Mg reacts with Li to form the Li-In alloy phase. Next, as shown in FIG. 2(c) and (d), when charging of the battery 10 progresses, a Li-Mg alloy phase is formed in addition to the Li-In alloy phase. Since the Li-In alloy phase is formed before the Li-Mg alloy phase, a state in which the Li-In alloy phase is dispersed in the Li-Mg alloy phase is obtained.

[0028] Next, as shown in FIG. 3(a), when the charged battery 10 is discharged, Li contained in the metal layer 2 moves to the positive electrode active material layer 4 through the electrolyte layer 3. At this time, since Mg has a lower reaction potential for Li insertion / extraction than In, Li is first desorbed from the Li-Mg alloy phase. As shown in FIG. 3(b), the Li-In alloy phase has high Li ion conductivity, so a good ion conduction path is formed. As shown in FIG. 3(c), it is presumed that the Li-In alloy phase is maintained even at the end of discharge, and this can suppress the increase in resistance in the negative electrode. As a result, it is presumed that good discharge capacity characteristics are obtained.

[0029] The battery in the present disclosure can be roughly divided into two embodiments according to the state of charge (SOC). Hereinafter, the battery in the present disclosure will be described in a first embodiment and a second embodiment.

[0030] 1. First embodiment 3(a), the battery 10 in the first embodiment has, in the thickness direction, a negative electrode current collector 1, a metal layer 2, an electrolyte layer 3, and a positive electrode active material layer 4, in this order. Furthermore, the metal layer 2 contains a Li-Mg alloy phase and a Li-In alloy phase.

[0031] (1) Negative electrode The negative electrode in the first embodiment has a negative electrode current collector. Examples of the material of the negative electrode current collector include SUS, copper, nickel, and carbon. Examples of the shape of the negative electrode current collector include a foil shape. The thickness of the negative electrode current collector is, for example, 1 μm or more and 500 μm or less.

[0032] The negative electrode has a metal layer. The metal layer contains a Li-Mg alloy phase and a Li-In alloy phase. The Li-Mg alloy phase is a metal phase of an alloy containing Li and Mg, and may be a metal phase of a binary alloy containing Li and Mg, or may be a metal phase of an alloy containing other elements in addition to Li and Mg. In the latter case, it is preferable that Li and Mg are the main components in the Li-Mg alloy phase. The "main component" refers to the component that has the highest proportion (at%) among the components contained in the metal phase. In the Li-Mg alloy phase, the total proportion of Li and Mg to all elements is, for example, 50 at% or more, may be 70 at% or more, or may be 90 at% or more.

[0033] The Li-In alloy phase is a metal phase of an alloy containing Li and In, and may be a metal phase of a binary alloy containing Li and In, or may be a metal phase of an alloy containing other elements in addition to Li and In. In the latter case, it is preferable that Li and In are the main components in the Li-In alloy phase. In the Li-In alloy phase, the total ratio of Li and In to all elements is, for example, 50 at% or more, may be 70 at% or more, or may be 90 at% or more.

[0034] The metal layer has both Li-In alloy phase and Li-Mg alloy phase. In particular, in the metal layer, the Li-In alloy phase is preferably dispersed in the Li-Mg alloy phase. That is, it is preferable that a sea-island structure is formed in which the Li-Mg alloy phase is the sea and the Li-In alloy phase is the island. This is because the increase in resistance in the negative electrode at the end of discharge can be suppressed. The size of the Li-In alloy phase is not particularly limited, but is, for example, 0.1 μm or more and 5 μm or less. The size of the Li-In alloy phase can be obtained from the distribution of In by SEM-EDX. The size of the Li-In alloy phase is the average value obtained by measuring the size of 100 or more samples.

[0035] In the metal layer, the ratio of In to the total of In and Mg (In / (In+Mg)) is not particularly limited. In / (In+Mg) is, for example, 5 at% or more, and may be 10 at% or more, 15 at% or more, 20 at% or more, or 25 at% or more. If the value of In / (In+Mg) is too small, the effect of improving the discharge capacity characteristics by In may not be fully exhibited. On the other hand, In / (In+Mg) is, for example, 90 at% or less, and may be 80 at% or less, 70 at% or less, or 60 at% or less. If the value of In / (In+Mg) is too large, the effect of improving the capacity retention rate by Mg may not be fully exhibited.

[0036] The metal layer preferably does not contain a conductive material. The metal layer preferably does not contain a binder. A Li phase may be formed inside the metal layer. A precipitated Li layer may be formed between the metal layer and the electrolyte layer. A precipitated Li layer may be formed between the metal layer and the negative electrode current collector.

[0037] The metal layer is usually a dense layer. The porosity of the metal layer (the ratio of the area of ​​voids in the cross section of the metal layer) is, for example, 5% or less, may be 3% or less, or may be 1% or less. In the first embodiment, the thickness of the metal layer is not particularly limited, but is, for example, 5 μm or more and 30 μm or less.

[0038] As shown in FIG. 3(a), the metal layer 2 may be in direct contact with the negative electrode current collector 1. Similarly, the metal layer 2 may be in direct contact with the electrolyte layer 3. On the other hand, although not particularly shown, another layer may be disposed between the metal layer and the negative electrode current collector. Similarly, another layer may be disposed between the metal layer and the electrolyte layer. Also, as shown in FIG. 3(c), the metal layer 2 after discharge may contain a Li-Mg alloy phase and a Li-In alloy phase. Depending on the SOC, the metal layer after discharge may contain a Mg phase not containing Li and a Li-In alloy phase. Similarly, the metal layer after discharge may contain a Mg phase not containing Li and an In phase not containing Li.

[0039] (2) Positive electrode The positive electrode in the first embodiment has a positive electrode current collector and a positive electrode active material layer. The positive electrode active material layer contains at least a positive electrode active material. The positive electrode active material layer may also contain at least one of an electrolyte, a conductive material, and a binder.

[0040] The positive electrode active material may be, for example, an oxide active material. Examples of the oxide active material include LiCoO2, LiNi 1 / 3 Co 1 / 3 Mn 1 / 3 O2, etc., rock salt layered active materials, LiMn2O4, Li4Ti5O 12 and olivine type active materials such as LiFePO4. The shape of the positive electrode active material may be, for example, particulate. The average particle size (D 50 ) is, for example, 0.5 μm or more and 50 μm or less. 50 ) refers to the volume cumulative particle size measured by a laser diffraction scattering type particle size distribution measuring device.

[0041] Examples of the electrolyte include solid electrolytes. Examples of the solid electrolyte include inorganic solid electrolytes such as sulfide solid electrolytes, oxide solid electrolytes, and halide solid electrolytes. The sulfide solid electrolyte preferably contains sulfur (S) as the main component of the anion element. The oxide solid electrolyte preferably contains oxygen (O) as the main component of the anion element. The halide solid electrolyte preferably contains a halogen (X) as the main component of the anion. Among these, the sulfide solid electrolyte is preferred.

[0042] The sulfide solid electrolyte preferably contains Li, M (M is at least one of P, Sn, Al, Zn, In, Ge, Si, Sb, Ga, and Bi), and S. The sulfide solid electrolyte may also contain halogen elements such as F, Cl, Br, and I. In the sulfide solid electrolyte, a portion of the S element may be substituted with O.

[0043] The sulfide solid electrolyte may be a glass-based (amorphous) sulfide solid electrolyte, a glass ceramic-based sulfide solid electrolyte, or a crystalline sulfide solid electrolyte. Examples of the crystalline phase contained in the sulfide solid electrolyte include an LGPS-type crystalline phase, a Thio-LISICON-type crystalline phase, and an Argyrodite-type crystalline phase.

[0044] Examples of sulfide solid electrolytes include Li2S-P2S5, Li2S-P2S5-LiI, Li2S-P2S5-GeS2, Li2S-P2S5-Li2O, Li2S-P2S5-Li2O-LiI, Li2S-P2S5-LiI-LiBr, Li2S-SiS2, Li2S-SiS2-LiI, Li2S-SiS2-LiBr, Li2S-SiS2-LiCl, Li2S-SiS2-B2S3-LiI, Li2S-SiS2-P2S5-LiI, Li2S-B2S3, and Li2S-P2S5-Z. m S n (where m and n are positive numbers. Z is Ge, Zn, or Ga.), Li2S-GeS2, Li2S-SiS2-Li3PO4, Li2S-SiS2-Li x MO y (where x and y are positive numbers, and M is P, Si, Ge, B, Al, Ga, or In.)

[0045] Other examples of the solid electrolyte include organic solid electrolytes such as polymer electrolytes, gel electrolytes, etc. Furthermore, a liquid electrolyte (electrolytic solution) can also be used as the electrolyte.

[0046] Examples of the conductive material include carbon materials. Examples of the carbon materials include particulate carbon materials such as acetylene black (AB) and ketjen black (KB); and fibrous carbon materials such as carbon fiber, carbon nanotubes (CNT) and carbon nanofibers (CNF). Examples of the binder include rubber-based binders such as butylene rubber (BR) and styrene butadiene rubber (SBR), and fluoride-based binders such as polyvinylidene fluoride (PVDF). The thickness of the positive electrode active material layer is, for example, 1 μm or more and 500 μm or less.

[0047] Examples of the material of the positive electrode current collector include SUS, aluminum, nickel, and carbon. Examples of the shape of the positive electrode current collector include a foil shape. The thickness of the positive electrode current collector is, for example, 1 μm or more and 500 μm or less.

[0048] (3) Electrolyte layer The electrolyte layer in the first embodiment contains at least an electrolyte. The electrolyte is the same as that described in the above "(2) Positive electrode". In particular, the electrolyte layer preferably contains a solid electrolyte as the electrolyte. That is, the electrolyte layer is preferably a solid electrolyte layer containing a solid electrolyte. A battery having a solid electrolyte layer may be called an all-solid-state battery. The solid electrolyte layer may contain a binder in addition to the solid electrolyte. The binder is the same as that described in the above "(2) Positive electrode". The thickness of the electrolyte layer is, for example, 1 μm or more and 500 μm or less.

[0049] (4)Battery The battery in the first embodiment has a negative electrode current collector, a metal layer, an electrolyte layer, and a positive electrode active material layer in this order in the thickness direction. In addition, the battery usually has an exterior body that houses these members. Examples of the exterior body include a laminate type exterior body and a case type exterior body.

[0050] The use of the battery is not particularly limited, but examples thereof include power sources for vehicles such as hybrid electric vehicles (HEVs), plug-in hybrid electric vehicles (PHEVs), electric vehicles (BEVs), gasoline-powered vehicles, and diesel-powered vehicles. In particular, the battery is preferably used as a driving power source for hybrid electric vehicles (HEVs), plug-in hybrid electric vehicles (PHEVs), or electric vehicles (BEVs). The battery may also be used as a power source for moving objects other than vehicles (for example, railways, ships, and aircraft), and may also be used as a power source for electrical appliances such as information processing devices.

[0051] 2. Second embodiment As shown in Fig. 2(a), the battery 10 in the second embodiment has a negative electrode current collector 1, a metal layer 2, an electrolyte layer 3, and a positive electrode active material layer 4, in this order in the thickness direction. Furthermore, the metal layer 2 contains an Mg-In alloy. Details of each member other than the metal layer 2 are the same as those described in the first embodiment above.

[0052] The metal layer contains an Mg-In alloy. The Mg-In alloy is an alloy containing Mg and In, and may be a binary alloy containing Mg and In, or an alloy containing other elements in addition to Mg and In. In the latter case, it is preferable that Mg and In are the main components in the Mg-In alloy. In the Mg-In alloy, the total ratio of Mg and In to all elements is, for example, 50 at% or more, may be 70 at% or more, or may be 90 at% or more.

[0053] The metal layer may have a metal phase of an Mg-In alloy (Mg-In alloy phase) and may contain Mg-In alloy particles. The Mg-In alloy particles have an average particle size D 50Preferably, the nanoparticles have a diameter of 1 μm or less. In the metal layer, the ratio of In to the total of In and Mg (In / (In+Mg)) is not particularly limited. The preferred range of In / (In+Mg) is the same as that described in the first embodiment. In addition, it is preferable that the metal layer does not contain a conductive material. In addition, it is preferable that the metal layer does not contain a binder. In addition, in the second embodiment, the metal layer usually does not contain Li.

[0054] The metal layer is usually a dense layer. The porosity of the metal layer (the ratio of the area of ​​voids in the cross section of the metal layer) is, for example, 5% or less, may be 3% or less, or may be 1% or less. The metal layer may be a vapor deposition film. The metal layer is preferably in close contact with the negative electrode current collector. That is, the metal layer is preferably arranged so as to cover the surface of the negative electrode current collector. A member having a negative electrode current collector and a metal layer arranged on the negative electrode current collector may be referred to as a coated current collector. In the second embodiment, the thickness of the metal layer is not particularly limited, but is, for example, 30 nm or more and 5 μm or less, and may be 100 nm or more and 3 μm or less, or may be 500 nm or more and 2 μm or less.

[0055] The battery in the second embodiment has a negative electrode current collector, a metal layer, an electrolyte layer, and a positive electrode active material layer in this order in the thickness direction. In addition, the battery usually has an exterior body that houses these members. The configuration other than the metal layer is the same as that described in "1. First embodiment" above.

[0056] B. Battery manufacturing method Fig. 4 is a flow diagram illustrating a method for manufacturing a battery according to the present disclosure. As shown in Fig. 4, a metal layer containing an Mg-In alloy phase is formed by vapor deposition (metal layer forming step). Then, a battery having a negative electrode current collector, a metal layer, an electrolyte layer, and a positive electrode active material layer in this order in the thickness direction is assembled (assembly step). This results in, for example, a battery 10 as shown in Fig. 1(a). Then, the battery is charged, and a Li-Mg alloy phase and a Li-In alloy phase are formed from the Mg-In alloy phase contained in the metal layer (charging step). This results in, for example, a battery 10 as shown in Fig. 1(b).

[0057] According to the present disclosure, by forming a specific metal layer, a battery having good discharge capacity characteristics can be obtained.

[0058] 1.Metal layer formation process The metal layer forming step in the present disclosure is a step of forming a metal layer including an Mg—In alloy phase by a vapor deposition method. The metal layer obtained by the vapor deposition method is a vapor deposition layer.

[0059] Examples of the vapor deposition method include physical vapor deposition (PVD) such as ion plating, sputtering, vacuum deposition, etc. It is preferable to prepare Mg metal and In metal separately and perform binary vapor deposition.

[0060] In the present disclosure, it is preferable to form a metal layer on the negative electrode current collector by a vapor deposition method. This is because the negative electrode current collector has high smoothness, and a metal layer of uniform thickness can be obtained. In this case, the metal layer may be formed directly on the negative electrode current collector. On the other hand, the metal layer may be formed on the negative electrode current collector via another layer (e.g., another vapor deposition layer). On the other hand, in the present disclosure, the metal layer may be formed on the solid electrolyte layer by a vapor deposition method. In this case, the metal layer may be formed directly on the solid electrolyte layer. On the other hand, the metal layer may be formed on the solid electrolyte layer via another layer (e.g., another vapor deposition layer).

[0061] 2. Assembly process The assembly process in the present disclosure is a process of assembling the battery having the negative electrode current collector, the metal layer, the electrolyte layer, and the positive electrode active material layer in this order in the thickness direction. The method of assembling the battery is not particularly limited, and a known method can be adopted.

[0062] 3.Charging process The charging step in the present disclosure is a step of charging the battery after the assembling step, and forming a Li-Mg alloy phase and a Li-In alloy phase from the Mg-In alloy phase contained in the metal layer. The charging conditions of the battery are appropriately selected depending on the configuration of the battery.

[0063] 4.Battery The battery obtained through the above-mentioned steps is the same as that described in "A. Battery."

[0064] The present disclosure is not limited to the above-described embodiment. The above-described embodiment is merely an example, and any configuration that is substantially the same as the technical idea described in the claims of the present disclosure and that exhibits similar effects is included in the technical scope of the present disclosure. EXAMPLES

[0065] [Example 1] (Preparation of positive electrode) Nickel cobalt lithium aluminum oxide (NCA) was prepared as the positive electrode active material, a Li2-P2S5-based sulfide solid electrolyte containing LiI and LiBr was prepared as the solid electrolyte (SE), a PVDF-based binder was prepared as the binder, and vapor grown carbon fiber (VGCF) was prepared as the conductive material. Next, each material was added to butyl butyrate in a weight ratio of NCA:SE:binder:conductive material=84.7:13.4:0.6:1.27 to obtain a positive electrode slurry. The obtained positive electrode slurry was applied to a positive electrode current collector (Al foil) with a coating gap of 225 μm, and then pre-dried at 60 ° C. and dried at 165 ° C. for 1 hour. As a result, a positive electrode having a positive electrode current collector and a positive electrode active material layer was obtained. The basis weight of the positive electrode active material layer was 18.7 mg / cm 2The designed capacity of the positive electrode active material layer is 3.0 mAh / cm 2 It was decided.

[0066] (Preparation of solid electrolyte layer) A Li2-P2S5-based sulfide solid electrolyte containing LiI and LiBr was prepared as the solid electrolyte (SE), and a PVDF-based binder was prepared as the binder. Next, each material was added to butyl butyrate in a weight ratio of SE:binder = 92.6:7.4 to obtain a slurry for the solid electrolyte layer. The obtained slurry was applied to a release film with a coating gap of 325 μm, and then temporarily dried at room temperature for 3 hours and dried at 165 ° C for 1 hour. This resulted in a laminate having a release film and a solid electrolyte layer. The obtained laminate was punched out to Φ14.5 mm, and the solid electrolyte layers of the two punched members were stacked on top of each other, and then pressed at a pressure of 7 ton. After pressing, the release films located on both sides were peeled off to obtain a free-standing solid electrolyte layer.

[0067] (Preparation of negative electrode) A stainless steel foil (SUS foil) was prepared as a negative electrode current collector. A metal layer (thickness 1.0 μm) containing an Mg-In alloy was formed on the SUS foil by binary deposition using an ion plating method. The target composition of the metal layer was Mg:In=90:10 (at% basis), and the actual composition was Mg:In=86:14 (at% basis). This resulted in a negative electrode having a negative electrode current collector and a metal layer.

[0068] (Preparation of evaluation cell) The obtained positive electrode was punched out to Φ11.28 mm, and the obtained negative electrode was punched out to Φ14.5 mm. A self-supporting solid electrolyte layer was placed between them, and an Al positive electrode tab and a Ni negative electrode tab were attached, and the laminate film was vacuum sealed. The sealed cell was subjected to a pressure of 392 MPa by cold isostatic pressing (CIP). After that, the cell was restrained at 1 MPa using a constant pressure jig with a spring inserted so that the restraining pressure was constant regardless of the volume change of the cell. This resulted in an evaluation cell.

[0069] [Example 2] Except for changing the target composition in the metal layer to Mg:In=67:33 (at %), an evaluation cell was obtained in the same manner as in Example 1. The actual composition in the metal layer was Mg:In=64:36 (at %).

[0070] [Example 3] Except for changing the target composition in the metal layer to Mg:In=50:50 (at %), an evaluation cell was obtained in the same manner as in Example 1. The actual composition in the metal layer was Mg:In=46:54 (at %).

[0071] [Example 4] Except for changing the target composition in the metal layer to Mg:In=33:67 (at %), an evaluation cell was obtained in the same manner as in Example 1. The actual composition in the metal layer was Mg:In=34:66 (at %).

[0072] [Example 5] Except for changing the target composition of the metal layer to Mg:In=10:90 (at %), an evaluation cell was obtained in the same manner as in Example 1. The actual composition of the metal layer was Mg:In=12:88 (at %).

[0073] [Comparative Example 1] An evaluation cell was obtained in the same manner as in Example 1, except that a metal layer containing Mg metal was formed as the metal layer.

[0074] [Comparative Example 2] An evaluation cell was obtained in the same manner as in Example 1, except that a metal layer containing In metal was formed as the metal layer.

[0075] [evaluation] (Charge / discharge test) For the evaluation cells obtained in Examples 1 to 5 and Comparative Examples 1 and 2, first, a constant current (current density: 0.15 mA / cm ) was applied in the cutoff voltage range of 4.2 V to 3.0 V. 2 , equivalent to 0.05C) - constant voltage (cutoff current density: 0.03mA / cm 2, equivalent to 0.01C) test, the evaluation cell was charged and discharged at 60°C.

[0076] Next, a cycle test was performed at a constant current (current density: 0.60 mA / cm) at 25°C with a cutoff voltage in the range of 4.2 V to 3.0 V. 2 , equivalent to 0.05C) - constant voltage (only when charging, cut-off current density: 0.03mA / cm 2 , equivalent to 0.01C) test was carried out. The results are shown in Fig. 5. The initial discharge capacity and the discharge capacity after 20 cycles in the cycle test are shown in Table 1 and Fig. 6.

[0077] [Table 1]

[0078] As shown in Table 1, FIG. 5 and FIG. 6, Examples 1 to 5 obtained higher discharge capacities than Comparative Examples 1 and 2. More specifically, as shown in FIG. 6, Examples 1 to 5 obtained higher discharge capacities than those estimated from the straight line connecting Comparative Examples 1 and 2. Among Examples 1 to 5, Examples 1 to 3 maintained high discharge capacities even after 20 cycles, and were confirmed to have excellent cycle characteristics. In particular, Examples 2 and 3 were confirmed to have significantly high initial discharge capacities and discharge capacities after 20 cycles.

[0079] (SEM observation) The cross-section of the evaluation cell obtained in Example 3 was observed by a scanning electron microscope (SEM). Specifically, the cell was initially charged at 60° C. under the same conditions as above, and the cross-section was observed by SEM using a secondary electron image at an applied voltage of 5 kV. The results are shown in FIG. 7. As shown in FIG. 7, the metal layer disposed between the solid electrolyte layer and the negative electrode current collector had increased from 1.0 μm before the initial charge to about 15 μm. This is because Mg and In contained in the metal layer were alloyed with Li. In addition, although not shown in particular, element mapping was analyzed by energy dispersive X-ray spectroscopy (EDX), and it was confirmed that Mg was relatively uniformly dispersed in the metal layer. In contrast, it was confirmed that In was locally dispersed. That is, it was confirmed that a sea-island structure was formed in which the Li-Mg alloy phase was the sea and the Li-In alloy phase was the island.

[0080] The reaction potential for Li insertion / extraction of Mg is 0.1V (vs Li / Li + ), and the reaction potential for Li insertion / extraction of In is 0.1V~0.6V (vs Li / Li + ) in consideration of this relationship. It is presumed that Li is first removed from the Li-Mg alloy phase during discharge, and that the Li-In alloy phase functions as a Li ion conductive path at that time, resulting in a high discharge capacity. In particular, it is presumed that in Example 3, the state of the locally dispersed Li-In alloy phase was effective for Li ion conduction. In addition, in consideration of the binary phase diagram of the Mg-In alloy, it is presumed that the Mg-In alloy in Example 3 (before the first charge) has a β″ phase and multiple other β phases, and that such a state influenced the dispersion state of the Li-In alloy phase after the first charge. [Explanation of symbols]

[0081] 1...Negative electrode current collector 2...metal layer 3...electrolyte layer 4...Cathode active material layer 5...Positive electrode current collector 10...battery

Claims

1. A battery that utilizes a deposition and dissolution reaction of metallic lithium as a negative electrode reaction, The negative electrode current collector, the metal layer, the electrolyte layer, and the positive electrode active material layer are arranged in this order in the thickness direction, The metal layer contains a Li-Mg alloy phase and a Li-In alloy phase.

2. 2. The battery according to claim 1, wherein in the metal layer, the Li-In alloy phase is dispersed relative to the Li-Mg alloy phase.

3. 2. The battery according to claim 1, wherein in the metal layer, a ratio of In to a total of In and Mg is 5 at % or more and 90 at % or less.

4. 2. The battery according to claim 1, wherein in the metal layer, a ratio of In to a total of In and Mg is 25 at % or more and 60 at % or less.

5. 2. The battery according to claim 1, wherein the size of the Li-Mg alloy phase is 0.1 μm or more and 5 μm or less.

6. 10. The battery of claim 1, wherein the metal layer does not contain a binder.

7. The battery according to claim 1 , wherein the electrolyte layer is a solid electrolyte layer containing a solid electrolyte.

8. 2. The battery of claim 1, wherein the solid electrolyte is a sulfide solid electrolyte.

9. A battery that utilizes a deposition and dissolution reaction of metallic lithium as a negative electrode reaction, The negative electrode current collector, the metal layer, the electrolyte layer, and the positive electrode active material layer are arranged in this order in the thickness direction, The battery, wherein the metal layer comprises a Mg—In alloy.

10. The battery according to claim 9 , wherein the metal layer has a metal phase of the Mg—In alloy (Mg—In alloy phase).

11. The battery of claim 10 , wherein the metal layer is a vapor-deposited layer.

12. The battery of claim 9, wherein the metal layer contains particles of the Mg-In alloy.

13. A method for manufacturing a battery using a deposition / dissolution reaction of metallic lithium as a negative electrode reaction, a metal layer forming step of forming a metal layer including an Mg—In alloy phase by a deposition method; an assembling step of assembling the battery having a negative electrode current collector, the metal layer, an electrolyte layer, and a positive electrode active material layer in this order in a thickness direction; A method for manufacturing a battery comprising the steps of:

14. The method for producing a battery according to claim 13, further comprising a charging step of charging the battery after the assembling step, to form a Li—Mg alloy phase and a Li—In alloy phase from the Mg—In alloy phase contained in the metal layer.

Citation Information

Patent Citations

  • Manufacture of nonaqueous electrolyte secondary battery

    JP1988178450A

  • All-solid battery and method for manufacturing the same

    JP2020184513A

  • All-solid battery

    JP2021051866A

  • Non-aqueous electrolyte storage element, device, and method for manufacturing non-aqueous electrolyte storage element

    JP2023076354A

  • Solid-state battery and manufacturing method of solid-state battery

    JP2024143042A